SnO2 Nanoparticles Decorated 2D Wavy Hierarchical Carbon Nanowalls with Enhanced Photoelectrochemical Performance - Khanis, N.H.; Ritikos, R.; Chiu, W.S.; Haw, C.Y.; Rashid, N.M.A.; Chia, M.Y.; Khiew, P.S.; Rahman, S.A. (Hindawi Publishing Corporation, 2017)
Two-dimensional carbon nanowall (2D-CNW) structures were prepared by hot wire assisted plasma enhanced chemical vapor deposition (hw-PECVD) system on silicon substrates. Controlled variations in the film structure were observed with increase in applied rf power during deposition which has been established to increase the rate of dissociation of precursor gases. The structural changes resulted in the formation of wavy-like features on the 2D-CNW, thus further enhancing the surface area of the nanostructures. The FESEM results confirmed the morphology transformation and conclusively showed the evolution of the 2D-CNW novel structures while Raman results revealed increase in ID/IG ratio indicating increase in the presence of disordered domains due to the presence of open edges on the 2D-CNW structures. Subsequently, the best 2D-CNW based on the morphology and structural properties was functionalized with tin oxide (SnO2) nanoparticles and used as a working electrode in a photoelectrochemical (PEC) measurement system. Intriguingly, the SnO2 functionalized 2D-CNW showed enhancement in both Mott-Schottky profiles and LSV properties which suggested that these hierarchical networks showed promising potential application as effective charge-trapping medium in PEC systems.